Psychological determinants and its association with coronary artery disease: a prospective study - Abdagire, Nitinkumar; Patil, Sandeep; Dalal, Dhaval; Singh, Harminder; Ojha, Soumya; Gawali, Vijaykumar (International Journal of Research in Medical Sciences, 2024)
Background: Psychological diseases like depression, anxiety and burnout are major public health problems of concern, as it is affecting both general as well as cardiac health. Therefore, present study aims to screen the patients for psychological determinants and its association with coronary artery disease. Methods: The study is prospective, questionnaire based, observational study conducted on 166 patients having coronary artery disease based on conventional coronary angiography. Out of 166 participants, 132 were in conventional risk factors Group (comorbid condition group), and 34 in non-conventional risk factors group (without any comorbid condition group). Patients were screened for depression, anxiety and burn out using the patient health questionnaire (PHQ-9), generalised anxiety disorder (GAD-7), burnout self-test questionnaires respectively. Results: The present study revealed majority of the participants had moderate anxiety, depression, and risk for burnout. Significant positive correlation was found between Syntax score and depression (P<0.05). No statistically significant difference was noted for anxiety, depression, and burnout score between comorbid group having conventional risk factors (patients having diabetes, hypertension and dyslipidaemia) and non-comorbid group with non-conventional risk factors (patients suffering from anxiety, depression and burnout without any comorbid conditions), suggesting major role of anxiety, depression, and burnout for the development of cardiovascular diseases. Conclusions: Non-conventional risk factors add increased risk for the development of coronary artery disease; therefore, efforts should also be made to assess cardiac patients for psychological determinants and to improve patients psychological and social function.